Public health and clinical impact of increasing emergency department-based HIV testing: perspectives from the 2007 conference of the National Emergency Department HIV Testing Consortium. - Kecojevic, Aleksandar; Lindsell, Christopher J; Lyons, Michael S; Holtgrave, David; Torres, Gretchen; Heffelfinger, James; Brown, Jeremy; Couture, Eileen; Jung, Julianna; Connell, Samantha; Rothman, Richard E (Annals of emergency medicine, 2011)
Understanding perceived benefits and disadvantages of HIV testing in emergency departments (EDs) is imperative to overcoming barriers to implementation. We codify those domains of public health and clinical care most affected by implementing HIV testing in EDs, as determined by expert opinion.
Keywords: Early Diagnosis; Emergency Service, Hospital; Focus Groups; Health Care Surveys; HIV Infections; Humans; Program Evaluation; Public Health; United States